A dual-band CMOS LC-VCO with highly linear frequency tuning characteristics. Issue 12 (December 2015) - Luo, Yanbin; Ma, Chengyan; Gan, Yebing; Qian, Min; Ye, Tianchun
Abstract: A dual-band wide range LC voltage controlled oscillator (VCO) with highly linear frequency tuning characteristics for GNSS application is presented. The linearity of VCO includes the coarse and fine tuning sensitivity variations, which are defined as the frequency step per-code ( f step ) variation and the VCO gain ( K VCO ) variation, respectively. Compared to the conventional circuit topology, the proposed VCO utilizes the 4-bit (Bit<3:0>) digital signal to control a varactors array instead of the switched capacitors bank to realize the linear coarse tuning. And the 4-bit digital signal also controls the other varactors array to reduce the variation of the VCO gain. Measurement results illustrate that the output frequency range covers the whole GNSS bands with f step and K VCO almost keeping constant. Thanks to the good linearity, the designed VCO obtains a low phase noise of −124 dBc/Hz at 1 MHz offset from 3.018 GHz output frequency while consuming only 5 mA from 1.8 V supply. The proposed circuit is fabricated in 0.18 μm CMOS process and the die area is 0.7 mm×0.7 mm.